Aplikasi Sensor Tgs 2620 Sebagai Pendeteksi Kadar Alkohol Pada Produk Pangan Berbasis Mikrokontroler Atmega 8535 - R Rohmanto; Amir Supriyanto; Gurum Ahmad Pauzi (Jurnal Teori dan Aplikasi Fisika, 2015)
It has been designed and fabricated a gauge levels of alcohol (C2H5OH) on microcontroller ATMega 8535 based food products using gas sensorTGS2620. Alcohol content measuring instrument has calibrated using to Alkoholmeter. Data from the sensors has processed by microcontroller which results displayed by the LCD16x2. The process of collecting, processing, and communication of data was set by microcontroller ATMega8535 program with BASCOM programming language. Measurements were made on samples in the form of a liquid mixture of alcohol and distilled water with 100mlevaporated. Measurements were performed in5repetitions. Calibration of the instrument that by taking the data from the sensor voltage fluids that have been in dilute alcohol. This gauge has a measurement range of 0% to 97% with a 4.9% error. As a food product samples that will be used in the application of this tool isBintang Bir Pilsanier Zero, Vodka Mixmax, Anker Beer, Pepsi Twist, Kratindaeng Energy Drink, Yogurt, Kecap, Permen Mints, Saos, Calpico Soda, Maya Sarden, and Tapai.